Effective Recognition of Caffeine by Diaminocarbazolic Receptors. Issue 7 (1st April 2020) - Francesconi, Oscar; Ienco, Andrea; Nativi, Cristina; Roelens, Stefano
Abstract: Caffeine is a competitive inhibitor of adenosine receptors and possesses wide pharmacological activity. Artificial receptors recognizing caffeine potentially have a wide range of biomedical and industrial applications. Herein, we describe two structurally related and readily available artificial receptors: 1) a macrocyclic receptor, which binds caffeine with the unprecedented affinity of 9.3 μM, though with poor selectivity; and 2) a tweezers‐like structure, showing an affinity of 26 μM and a 4.5‐fold and 6‐fold selectivity compared to theophylline and theobromine, respectively. Binding affinities were measured by 1 H NMR titrations and were confirmed by isothermal titration calorimetry. The X‐ray structure of the complex between caffeine and the acyclic receptor revealed the origin of the recognition, explained the selectivity, and shed light on the role of hydrogen bonding and CH−π/π–π interactions. Abstract : Tweezers for caffeine : Caffeine is a pharmacologically active drug that requires a well‐designed receptor to be effectively and selectively recognized among structurally related xanthines. Here we report two structures, a macrocyclic receptor, showing an outstanding affinity of 9.3 μM for caffeine but a poor selectivity, and a tweezers‐like receptor, binding caffeine with a 26 μM affinity but a significant selectivity compared to theophylline and theobromine.